Comparison of Cleaning Efficacy and Instrumentation Time of Reciproc and Mtwo Rotary Systems in Primary Molars - Kiumars Nazari Moghaddam; Hamideh Farajian Zadeh; Nafiseh Farajian Zadeh (Islamic Dental Association of Iran, 2017)
Background and Aim: Pulpectomy of primary teeth is commonly performed with hand files and instruments. However, it is a time consuming procedure. Compared to hand files, rotary instrumentation has more advantages. The purpose of this in vitro study was to compare the cleaning efficacy and time taken for instrumentation of deciduous mo-lars using Reciproc and Mtwo rotary systems. Materials and Methods: In this experimental study, 96 canals of 28 extracted primary molars with at least two-thirds of intact roots, with no previous treatment and 7-12 mm length were selected. After access cavity preparation, size #15 K-file was introduced into the root canal and India ink was injected with an insulin syringe. Then, 96 samples were randomly divided into two experimental groups and one control group. In group I (n=44), root canals were prepared with Reciproc; in group II (n=44), Mtwo files were used for instrumentation, and in group III, eight samples were considered as negative controls. After clearing and root sectioning, the removal of India ink in the cervical, middle, and apical thirds was scored. Data were analyzed using Student's t-test and Mann-Whitney U test. Results: There was no significant difference between the experimental groups regarding cleaning efficacy at the apical third of root canals (P>0.05). The coronal and middle thirds scored higher in the Reciproc group (P<0.05). Instrumentation with Reciproc rotary files was significantly less time consuming (P<0.001). Conclusion: Using new systems such as Reciproc file for pulpectomy of primary teeth is beneficial.